Analisis Fungsi Sintaksis dan Nilai di Dalam Pepatah Bahasa Indonesia - Br Ginting, Epril Linia; Madia, I Made; Mas Triadnyani, I G.A.A. (Humanis, 2022)
This study discusses syntactic functions, cultural values and national character in Indonesian proverbs. Problems discussed in  study (1) what is form of Indonesian proverb.  (2) what are  values (education in the culture and character of  nation) contained in the Indonesian proverb (3) what are  aspects of  social meaning of the Indonesian proverb.  Method of data collection in this study is  method of listening, technique used is  technique of note taking.  theories used are syntax and ethnolinguistics.  Data analysis carried out was concluded from  number of clauses in Indonesian proverbs grouped into single sentence proverbs and complex sentence proverbs. Based on  implementation of ethnolinguistic theory referring to Permendiknas 2010 resulted in eighteen values of cultural education and national character.  social aspect   Indonesian proverb is divided into two parts, (1)  reflection of society contained in  form of advice in  proverb and (2)  social function in  form of moral values contained in  proverb.